CARICOM's e-agriculture strategies - Kalloo, Margaret (Technical Centre for Agricultural and Rural Cooperation, 2013)
The Caribbean Community is transforming its agricultural sector into a competitive and sustainable system of agricultural production and services in which ICTs will play a vital role